A Standardized Protocol for the Management of Appendicitis in Children Reduces Resource Utilization. Issue 6 (November 2020) - Pennell, Christopher; Meckmongkol, Teerin; Arthur, L. Grier; Ciullo, Sean; Prasad, Rajeev; Lindholm, Erika; Grewal, Harsh
Abstract : Introduction: Appendicitis is the most common condition requiring emergency surgery in children. We implemented a standardized protocol (SP) for treating children with appendicitis to provide more uniform care and reduce resource utilization. Methods: All patients younger than 21 years were managed with the SP beginning in January 2017. We compared data from 22 months before and after implementation. The primary outcomes included the length of stay (LOS), antibiotic days, discharge on intravenous antibiotics, utilization of peripherally inserted central catheters lines, and postoperative imaging. Secondary outcomes were protocol adherence and the rates adverse events, including postoperative abscess, return to emergency department or operating room, surgical site infection, and readmission. Results: Protocol adherence was 92.3%. For uncomplicated cases (n = 412), LOS ( P = 0.010) and postoperative antibiotic days ( P < 0.001) were significantly reduced. There was no difference in the rates of any adverse event (6.7% versus 2.7%; P = 0.058), postoperative abscess (0.4% versus 0.0%; P = 0.544), return to emergency department (6.3% versus 2.7%; P = 0.084), readmission (1.8% versus 0.5%; P = 0.245), or postoperative ultrasound (0.4% versus 0.5%; P = 0.705) and computed tomography (0.0% versus 0.5%; P = 0.456). For complicated cases (n = 229), the post-SP cohort had a shorter LOS ( P = 0.015), fewer peripherally inserted central catheters lines (26.9% versus 2.7%; P < 0.001), fewer postoperative ultrasounds (8.4% versus 1.8%; P = 0.027), and fewer discharges on intravenous antibiotics (17.6% versus 0.9%; P < 0.001). There were no differences in adverse events before and after the SP (16.0% versus 18.3%; P = 0.633). Conclusion: Implementing an SP for appendicitis in children reduced resource utilization, and by inference healthcare costs, for both uncomplicated and complicated cases without adversely affecting clinical outcomes.